1996
DOI: 10.1017/s0952523800007793
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of VEP intermodulation and second harmonic components by dichoptic, monocular, and binocular stimulation

Abstract: Modulation by two temporal frequencies differentiates visual processing at the fundamentals (lFs), second harmonics (2Fs), and second-order intermodulation components (IMCs), the latter created neurally as the sum or difference of the two modulation frequencies. Steady-state VEPs were recorded while stereo-normal adults viewed luminance or grating stimuli modulated by up to three temporal frequencies under dichoptic, monocular, or ordinary (binocular) viewing conditions arranged using liquid crystal light shut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…First, they demonstrated how IMs provide a direct physiological measure of neural signal integration in the human brain. For example, several studies investigating early integration from both eyes demonstrated large differences in IM responses when the two eyes receive the same input (monoptic presentation), when only one eye receives input (monocular presentation) and when the two eyes receive different inputs (dichoptic presentation) (Suter et al, 1996) or, when comparing between healthy and stereoblind patients (Baitch and Levi, 1988). Second, they demonstrated how plausible their models of neural processes can be by examining the response spectrum across frequencies (including harmonics and high order IMs, as detailed above in the section 3.3) (Regan and Regan, 1988a).…”
Section: Low-and Mid-level Visual Processingmentioning
confidence: 99%
“…First, they demonstrated how IMs provide a direct physiological measure of neural signal integration in the human brain. For example, several studies investigating early integration from both eyes demonstrated large differences in IM responses when the two eyes receive the same input (monoptic presentation), when only one eye receives input (monocular presentation) and when the two eyes receive different inputs (dichoptic presentation) (Suter et al, 1996) or, when comparing between healthy and stereoblind patients (Baitch and Levi, 1988). Second, they demonstrated how plausible their models of neural processes can be by examining the response spectrum across frequencies (including harmonics and high order IMs, as detailed above in the section 3.3) (Regan and Regan, 1988a).…”
Section: Low-and Mid-level Visual Processingmentioning
confidence: 99%
“…In addition to self-term responses, the interaction between the two unique frequency components presented to each eye also evokes intermodulation (IM) terms (nF1 Ϯ mF2) (Baitch and Levi, 1988;Suter et al, 1996;Brown et al, 1999;Sutoyo and Srinivasan, 2009;Baker and Wade, 2017;Cunningham et al, 2017). The presence of such IM components constitutes objective neural evidence for interocular interaction (Brown et al, 1999; for review, see Norcia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques use distinct temporal frequencies in each eye 12, 35, 37 . With these latter methods, responses of each eye are recorded simultaneously at harmonics of the respective eye-tagging frequencies and definitive evidence for binocular interaction can be obtained by detecting responses at frequencies equal to sums and difference of the eye-tag frequencies.…”
Section: Discussionmentioning
confidence: 99%